A tale of three approaches: Leveraging organizational discourse analysis, relational event modeling, and dynamic network analysis for collective leadership. (April 2020) - Maupin, Cynthia K; McCusker, Maureen E; Slaughter, Andrew J; Ruark, Gregory A
How can we enhance theory-method alignment when studying collective leadership? We propose that leveraging methodological approaches that are powerful enough to address three primary challenges of collective leadership—the incorporation of time, context, and multiple levels—will promote a more robust body of collective leadership research and practice. In particular, we review and integrate three complementary methodological approaches—organizational discourse analysis, relational event modeling, and dynamic network analysis—which have the flexibility to address these challenges. The purpose of this article is to demonstrate the utility of these methodological approaches for addressing major methodological challenges within the field of collective leadership. Through this effort, we aim to facilitate conversation across disparate streams of research and encourage researchers to explore how novel research questions and perspectives might be advanced through leveraging these methods, either in isolation or in combination.